Grafting and Early Expression of Growth Factors from Adipose-Derived Stem Cells Transplanted into the Cochlea, in a Guinea Pig Model of Acoustic Trauma - Fetoni, Anna Rita; Lattanzi, Wanda; Eramo, Sara Letizia Maria; Barba, Marta; Paciello, Fabiola; Moriconi, Chiara; Rolesi, Rolando; Michetti, Fabrizio; Troiani, Diana; Paludetti, Gaetano (Frontiers in Cellular Neuroscience, 2014)
Noise exposure causes damage of multiple cochlear cell types producing permanent hearing loss with important social consequences. In mammals, no regeneration of either damaged hair cells or auditory neurons has been observed and no successful treatment is available to achieve a functional recovery. Several evidences indicate adipose-derived stem cells (ASCs) as promising tools in diversified regenerative medicine applications, due to the high degree of plasticity and trophic features. This study was aimed at identifying the path of in vivo cell migration and expression of trophic growth factors, upon ASC transplantation into the cochlea, following noise-induced injury. ASCs were isolated in primary culture from the adipose tissue of a guinea pig, transduced using a viral vector to express the green fluorescent protein, and implanted into the scala tympani of deafened animals. Auditory function was assessed 3 and 7 days after surgery. The expression of trophic growth factors was comparatively analyzed using real time PCR in control and noise-injured cochlear tissues. Immunofluorescence was used to assess the in vivo localization and expression of trophic growth factors in ASCs and cochleae, 3 and 7 days following homologous implantation. ASC implantation did not modify auditory function. ASCs migrated from the perilymphatic to the endolymphatic compartment, during the analyzed time course. Upon noise exposure, the expression of chemokine ligands and receptors related to the PDGF, VEGF and TGFbeta pathways, increased in the cochlear tissues, possibly guiding in vivo cell migration. Immunofluorescence confirmed the increased expression, which appeared to be further strengthened by ASC implantation. These results indicate that ASCs are able to migrate at the site of tissue damage and express trophic factors, upon intracochlear implantantion, providing an original proof of principle, which could pave the way for further developments of ASC-based treatments of deafness.